+0  
 
+2
58
2
avatar+27 

1. A3(A3+A2)-1+A2(A2+A)-1+2(A3+A2)-1A4

 

2. -2 A-2(A-2+A-3)-1+2A3(A2+A3)-1+ 3/4 A(A-1+I)-1+ 3/4 A3(A+I)-1

 

Thanks!

syncstar  Aug 15, 2017
Sort: 

2+0 Answers

 #1
avatar+18564 
+1

1. A3(A3+A2)-1+A2(A2+A)-1+2(A3+A2)-1A4

Question see also:

http://web2.0calc.com/questions/matrix-problem-simplify-as-little-as-possible-each_1

 

\(\begin{array}{|rcll|} \hline && A^3(A^3+A^2)^{-1}+A^2(A^2+A)^{-1}+2(A^3+A^2)^{-1}A^4 = \ ?\\ \hline \end{array}\)

 

1.

\(\begin{array}{|rcll|} \hline &&\mathbf{ A^3(A^3+A^2)^{-1} } \\ &=& A^3[ AA^2+IA^2 ]^{-1} \quad & | \quad \text{Identity matrix I }\\ &=& A^3[ (A+I)A^2 ]^{-1} \quad & | \quad \text{Formula:} \quad (AB)^{-1} = B^{-1}A^{-1}\\ &=& A^3[ (A^2)^{-1}(A+I)^{-1} ] \quad & | \quad (A^2)^{-1} = (AA)^{-1} = A^{-1}A^{-1} = (A^{-1})^2 \\ &=& A^3(A^{-1})^2(A+I)^{-1} \quad & | \quad \\ &=& AA^2(A^{-1})^2(A+I)^{-1} \quad & | \quad A^2(A^{-1})^2 = I \\ &=& AI(A+I)^{-1} \quad & | \quad AI = A \\ &\mathbf{=}& \mathbf{ A(A+I)^{-1} } \\ \hline \end{array}\)

 

2.

\(\begin{array}{|rcll|} \hline &&\mathbf{ A^2(A^2+A)^{-1} } \\ &=& A^2(AA+IA)^{-1} \quad & | \quad \text{Identity matrix I } \\ &=& A^2[(A+I)A]^{-1} \quad & | \quad \text{Formula:} \quad (AB)^{-1} = B^{-1}A^{-1} \\ &=& A^2[A^{-1}(A+I)^{-1} ] \\ &=& AAA^{-1}(A+I)^{-1} \quad & | \quad AA^{-1} = I \\ &=& AI(A+I)^{-1} \quad & | \quad AI = A \\ &\mathbf{=}& \mathbf{ A(A+I)^{-1} } \\ \hline \end{array} \)

 

3.

\(\begin{array}{|rcll|} \hline &&\mathbf{ 2(A^3+A^2)^{-1}A^4 }\\ &=& 2[ A^2A+A^2I ]^{-1}A^4 \quad & | \quad \text{Identity matrix I } \\ &=& 2[ A^2(A+I) ]^{-1}A^4 \quad & | \quad \text{Formula:} \quad (AB)^{-1} = B^{-1}A^{-1} \\ &=& 2[ (A+I)^{-1}(A^2)^{-1} ] A^4 \quad & | \quad (A^2)^{-1} = (AA)^{-1} = A^{-1}A^{-1} = (A^{-1})^2 \\ &=& 2(A+I)^{-1}(A^{-1})^2 A^4 \\ &=& 2(A+I)^{-1}(A^{-1})^2 A^2A^2 \quad & | \quad (A^{-1})^2 A^2 = I \\ &=& 2(A+I)^{-1}IA^2 \quad & | \quad IA^2 = A^2 \\ &\mathbf{=}& \mathbf{ 2(A+I)^{-1}A^2 } \\ \hline \end{array}\)

 

summary

\(\begin{array}{|rcll|} \hline && A^3(A^3+A^2)^{-1}+A^2(A^2+A)^{-1}+2(A^3+A^2)^{-1}A^4 \\ &=& \mathbf{ A(A+I)^{-1} } + \mathbf{ A(A+I)^{-1} } + \mathbf{ 2(A+I)^{-1}A^2 } \\ &=& 2A(A+I)^{-1} + 2(A+I)^{-1}A^2 \\ &=& 2A(A+I)^{-1}I + 2(A+I)^{-1}A^2 \quad & | \quad I = A^{-1}A \\ &=& 2A(A+I)^{-1}A^{-1}A + 2(A+I)^{-1}A^2 \\ &=& [A(A+I)^{-1}A^{-1} + (A+I)^{-1}A]\ 2A \quad & | \quad A(A+I)^{-1} = [(A+I)A^{-1} ]^{-1} \\ &=& \{ [(A+I)A^{-1} ]^{-1} A^{-1} + (A+I)^{-1}A \} \ 2A \quad & | \quad (A+I)^{-1}A = [A^{-1}(A+I)]^{-1} \\ &=& \{ [(A+I)A^{-1} ]^{-1} A^{-1} + [A^{-1}(A+I)]^{-1} \} \ 2A \\ &=& [ (AA^{-1}+IA^{-1})^{-1} A^{-1} + (A^{-1}A+A^{-1}I)^{-1} ] \ 2A \quad & | \quad AA^{-1} = A^{-1}A = I \qquad IA^{-1} = A^{-1}I = A^{-1} \\ &=& [ (I+A^{-1})^{-1} A^{-1} + (I+A^{-1})^{-1} ] \ 2A \\ &=& [ (I+A^{-1})^{-1} (A^{-1} + I ) ] \ 2A \\ &=& [ (I+A^{-1})^{-1} (I+A^{-1} ) ] \ 2A \quad & | \quad (I+A^{-1})^{-1} (I+A^{-1} ) = I \\ &=& I 2A \\ &\mathbf{=}& \mathbf{ 2A } \\ \hline \end{array} \)

 

laugh

heureka  Aug 21, 2017
edited by heureka  Aug 21, 2017
edited by heureka  Aug 21, 2017
 #2
avatar+18564 
+1

2. -2 A-2(A-2+A-3)-1+2A3(A2+A3)-1+ 3/4 A(A-1+I)-1+ 3/4 A3(A+I)-1

 

\(\begin{array}{|rcll|} \hline && -2 A^{-2}(A^{-2}+A^{-3})^{-1}+2A^3(A^2+A^3)^{-1}+ \frac34 A(A^{-1}+I)^{-1}+ \frac34 A^3(A+I)^{-1} = \ ?\\ \hline \end{array} \)

 

1.
\(\small{ \begin{array}{|rcll|} \hline &&\mathbf{ -2 A^{-2}(A^{-2}+A^{-3})^{-1}+2A^3(A^2+A^3)^{-1} } \\\\ && & (A^{-2}+A^{-3})^{-1} = [(A^{-1}+I)A^{-2}]^{-1} \\ && & (A^{2}+A^{3})^{-1} = [(A+I)A^{2}]^{-1} \\\\ &=& -2 A^{-2}[(A^{-1}+I)A^{-2}]^{-1}+2A^3[(A+I)A^{2}]^{-1} \quad & | \quad A^{-2} = A^{-1}A^{-1} = (AA)^{-1} = (A^2)^{-1} \\ &=& -2 A^{-2}[(A^{-1}+I)(A^2)^{-1}]^{-1}+2A^3[(A+I)A^{2}]^{-1} \quad & | \quad [(A^{-1}+I)(A^2)^{-1}]^{-1} = [A^2(A^{-1}+I)^{-1}] \\ &=& -2 A^{-2}[A^2(A^{-1}+I)^{-1}]+2A^3[(A+I)A^{2}]^{-1} \\ &=& -2 A^{-2}A^2(A^{-1}+I)^{-1}+2A^3[(A+I)A^{2}]^{-1} \quad & | \quad A^{-2}A^2 = A^{-1}A^{-1}AA = A^{-1}(A^{-1}A)A = A^{-1}(I)A = A^{-1}A = I \\ &=& -2 I(A^{-1}+I)^{-1}+2A^3[(A+I)A^{2}]^{-1} \\ &=& -2 (A^{-1}+I)^{-1}+2A^3[(A+I)A^{2}]^{-1} \quad & | \quad [(A+I)A^{2}]^{-1} = [(A^2)^{-1}(A+I)^{-1} ] \\ &=& -2 (A^{-1}+I)^{-1}+2A^3[(A^2)^{-1}(A+I)^{-1} ] \quad & | \quad (A^2)^{-1} = A^{-2} \\ &=& -2 (A^{-1}+I)^{-1}+2A^3A^{-2}(A+I)^{-1} \\ &=& -2 (A^{-1}+I)^{-1}+2AA^2A^{-2}(A+I)^{-1} \quad & | \quad A^2A^{-2} = I \\ &=& -2 (A^{-1}+I)^{-1}+2AI(A+I)^{-1} \\ &=&\color{red}{ -2 (A^{-1}+I)^{-1}+2A(A+I)^{-1} } \quad & | \quad A(A+I)^{-1} = [(A+I)A^{-1} ]^{-1} \\ &=& -2 (A^{-1}+I)^{-1}+2[(A+I)A^{-1} ]^{-1} \\ &=& -2 (A^{-1}+I)^{-1}+2(AA^{-1}+IA^{-1} )^{-1} \\ &=& -2 (A^{-1}+I)^{-1}+2(I+A^{-1} )^{-1} \\ &=& -2 (A^{-1}+I)^{-1}+2(A^{-1}+I )^{-1} \\ &=& \mathbf{0} \\\\ && \mathbf{ -2 A^{-2}(A^{-2}+A^{-3})^{-1}+2A^3(A^2+A^3)^{-1} } = 0 \\ \hline \end{array} }\)

 

2.

\(\begin{array}{|rcrcl|} \hline && \mathbf{ -2 A^{-2}(A^{-2}+A^{-3})^{-1}+2A^3(A^2+A^3)^{-1} } \\ &=& \color{red}{-2 (A^{-1}+I)^{-1}+2A(A+I)^{-1}} & =& 0 \\ && -2 (A^{-1}+I)^{-1}+2A(A+I)^{-1} & =& 0 \\ && 2 (A^{-1}+I)^{-1} &=& 2A(A+I)^{-1} \\ && \mathbf{(A^{-1}+I)^{-1}} &\mathbf{=}& \mathbf{ A(A+I)^{-1}} \\ \hline \end{array}\)

 

3.

\(\begin{array}{|rcll|} \hline && -2 A^{-2}(A^{-2}+A^{-3})^{-1}+2A^3(A^2+A^3)^{-1}+ \frac34 A(A^{-1}+I)^{-1}+ \frac34 A^3(A+I)^{-1} \\ &=& 0 + \frac34 A(A^{-1}+I)^{-1}+ \frac34 A^3(A+I)^{-1} \\ &=& \frac34 A\underbrace{(A^{-1}+I)^{-1}}_{=A(A+I)^{-1}}+ \frac34 A^3(A+I)^{-1} \\ &=& \frac34 AA(A+I)^{-1}+ \frac34 A^3(A+I)^{-1} \\ &=& \frac34 A^2(A+I)^{-1}+ \frac34 A^3(A+I)^{-1} \\ &=& \frac34 ( A^2 + A^3)(A+I)^{-1} \\ &=& \frac34 A^2(I+A)(A+I)^{-1} \\ &=& \frac34 A^2\underbrace{(I+A)(I+A)^{-1}}_{=I} \\ &=& \frac34 A^2 I \\ &\mathbf{=}& \mathbf{\frac34 A^2 } \\ \hline \end{array} \)

 

laugh

heureka  Aug 21, 2017

13 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details